A Systems Framework for Infrastructure Business Models for Resilient and Sustainable Urban Areas - Walsh, Claire L.; Glendinning, Stephanie; Dawson, Richard J.; O'Brien, Peter; Heidrich, Oliver; Rogers, Christopher D. F.; Bryson, John R.; Purnell, Phil (Frontiers in Sustainable Cities, 2022)
Sustainable Development Goal 11 calls for inclusive, safe, resilient and sustainable cities. Urban areas comprise interconnected infrastructure systems that deliver services that support all aspects of daily life. Despite their important contribution to modern life current infrastructure business models typically under-estimate the long-term economic, social and environmental benefits of infrastructure. Therefore, new infrastructure business models are required that: (i) target urban areas or regions at a local scale where there is the greatest scope for innovation, (ii) target specific challenges or needs (i.e. where there is a clear driver for innovation), and (iii) tackle the issue of the flawed economic cost-benefit model for assessing the viability of infrastructure investments. This paper presents a framework that enables promotes multiple stakeholders to working together, and by focussing on outcomes to develop alternative infrastructure solutions and business models that deliver multiple values to multiple stakeholders. By explicitly mapping these values over time and space, the interdependencies between infrastructures are revealed, along with an expanded perception of the value being brought about by that infrastructure. Moreover, the broader consideration of value also increases the number of stakeholders beneficiaries, the value network, and subsequently identify how they can support the infrastructure intervention by formulating alternative funding and financing mechanisms. A sSeries of case studies to achieve resilience, sustainability and regeneration outcomes are used to show how the framework can be utilised to unlock investment in infrastructure in situations where traditional approaches have failed.